Primary cervical lymph nodal leishmaniasis. (October 2021) - Rodrigues, Gabriel; Raj, Pulak; Monappa, Vidya; Gowda, Chiranth; Carnelio, Sunitha
Leishmaniasis, an endemic disease in several parts of India, is a parasitic disease caused by protozoa and transmitted by the sandfly. Although cutaneous and visceral varieties are common, isolated lymph nodal involvement is extremely rare, and the diagnosis is often delayed owing to its uncommon presentation and lack of awareness of this possibility. We present a 72-year-old woman with asymptomatic right facial lymphadenopathy which on biopsy revealed leishmaniasis and responded well to drug therapy.